Programa de manejo de quelônios Amazônicos "pé-de-pincha": articulando a alfabetização científica em comunidades rurais do Baixo Amazonas - Rocha, João Marinho da (2012)
Historically the Amazon region was marked by violent dialogue processes on the actions that explored and enjoyed their natural resources. Currently, however, there are initiatives that actually demonstrate that local people also look at the world and say what, and how they see their world, assist in the care and use of its resources. One of these initiatives is the program "pé-de-pincha" that promotes the management of Amazonian turtles in partnership with communities, schools and the Federal University of Amazonas (UFAM) – in the lower Amazon Basin. This study shows how this dialogue helps processes of science literacy in subjects who participate in the actions of this program; using the ideas discussed in: Lorenzetti & Delizoicov (2001), Daniel (2005) and (2008), Pozo & Crespo (2009), Delizoicov, Angnotti, Pernambuco (2009) Almeida (2010), Saints (2010), Sandín Esteban (2010) & Krasilchik Marandino (2010), rock & Fachín-Terán (2010), Alcântara & Fachín-Terán (2010), Chassot (2011), in addition to others as well. The analysis was based on a qualitative research proposal. Using features such as participant observation and interviews, we bring the community knowledge concerning management issues in which they are inserted and in that sense give this knowledge to promote science literacy in teachers and pupils of the fourth and fifth years of the initial series of three schools. The analysis of their reports point to a huge sensitivity about the management, their relationships with community life and, above all, with educational activities from nonformal education, spaces generated by Community action to deal with the Amazonian resources. Signs that are indicative of science literacy in rural communities in the Amazon, are noted, not only from within the school, but the numerous non-formal community interactions and everyday experiences of men and women of Amazonian environments.